2015
DOI: 10.1155/2015/598134
|View full text |Cite
|
Sign up to set email alerts
|

Growth Pattern of Clear Cell Renal Cell Carcinoma in Patients with Delayed Surgical Intervention: Fast Growth Rate Correlates with High Grade and May Result in Poor Prognosis

Abstract: Objectives. Previous studies revealed an unclear correlation between the growth rate of renal cell carcinoma (RCC) and tumor grade and did not focus on certain histological subtype. This report investigated the correlation between the growth rate and tumor grade in clear cell RCC (ccRCC). Methods. We reviewed 60 patients with 61 ccRCC confirmed by delayed surgeries after at least 12 months of active surveillance. The linear growth rate (LGR), volumetric growth rate (VGR), and volume doubling time (VDT) were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
(31 reference statements)
2
10
1
Order By: Relevance
“…Given the fact that predictors of rapid tumor growth rate remain elusive (7), we further investigated the factors related to the growth rate. A study conducted by Kouba et al reported a faster growth rate in young patients than in old patients (17); however, our previous study (11) and this study failed to identify a correlation between age and growth rate in either group.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Given the fact that predictors of rapid tumor growth rate remain elusive (7), we further investigated the factors related to the growth rate. A study conducted by Kouba et al reported a faster growth rate in young patients than in old patients (17); however, our previous study (11) and this study failed to identify a correlation between age and growth rate in either group.…”
Section: Discussioncontrasting
confidence: 75%
“…Natural history and growth kinetics of clear cell renal cell carcinoma in sporadic and von Hippel-Lindau disease investigated the growth kinetics of sporadic clear cell renal cell carcinoma (ccRCC) (7)(8)(9)(10)(11) and ccRCC in von Hippel-Lindau (VHL) disease (12)(13)(14)(15); however, the difference in growth kinetics between the two groups is not well understood. Hence, the aim of our study was to further evaluate and compare the growth kinetics of sporadic ccRCC with those of ccRCC in VHL disease.…”
Section: Original Articlementioning
confidence: 99%
“…(17,51) A recent study also showed that a faster linear and volume growth rate and a shorter volume doubling time significantly correlates with a higher grade histology for clear cell RCCs under AS. (52) No standardized criteria to indicate delayed intervention during AS have been yet defined. However, reaching a diameter of 3-4 cm or a tumor volume doubling time <12 months under surveillance are generally used to identify renal masses at greatest risk of progression which should be conveyed to an active treatment.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…ccRCC ranks first in incidence amongst all histological types of kidney malignancies (19), and accounts for nearly 3% of all types of adult malignancies (20). Although the 5-year survival rate of patients with ccRCC at the early stage is >90%, it decreases to 10% in patients with advanced ccRCC (5), and >100,000 patients succumb to ccRCC per year worldwide (21). Therefore, it is imperative to identify tumor-specific markers for risk stratification that may be utilized for assessing the prognosis of patients, and which may facilitate the development of novel strategies for the diagnosis and therapy of ccRCC.…”
Section: Discussionmentioning
confidence: 99%